Our experience in the treatment of botulism - Ranković, Aleksandar; Vrbić, Miodrag; Jovanović, Maja; Popović Dragonjić, Lidija; Nedin Ranković, Gorana (Vojnosanitetski pregled, 2017)
Introduction. Botulism is a neuro -intoxication caused by a toxin secreted by Clostridium botulinum. Due to extremely high toxicity and lethality, this toxin can be used as an agent in a biological warfare. Case report. We presented six patients, mean age 28.8 years, who ate canned food and in whom the diagnosis of disease was made based on the typical clinical picture. Predominant symptoms were blurred vision, double vision (diplopia), dry mouth and constipation which were present in all patients. The patient whose disease was recognized only after 23 days and who did not receive the anti botulinum serum underwent the longest hospital treatment. All the patients received antibiotics and 4 patients received antitoxin. Neostigmine and enemas were used for the treatment of the disorder of intestinal motility and constipation. Conclusion. The diagnosis of botulinum was made based on afebrility, preserved states of consciousness, double vision, dry mouth and history data on consumption of suspicious food. Polyvalent serum anti botulinum should be applied as soon as possible because it reduces the occurrence of complications, length of hospital stay and mortality rate.